Recent Advances in Sorghum Improvement Research at ICRISAT - Belum V.S. Reddy; A. Ashok Kumar; P. Sanjana Reddy (Agriculture and Natural Resources, 2010)
Sorghum (Sorghum bicolor (L.) Moench) is one of the most important cereal crops widely grown for food, feed, fodder, forage and fuel in the semi-arid tropics of Asia, Africa, the Americas and Australia. In spite of rapid decreases in the area of sorghum in Asia, the production level has been maintained owing to the adoption of high yielding hybrids. Though impressive progress has been made in improving the sorghum cultivars for resistance to biotic and abiotic challenges, grain mold, shoot fly and terminal drought haunt sorghum growers across Asia. The International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and national programs in India, China and Thailand are working on genetic enhancement of sorghum for high yield, grain mold and shortly resistance. In addition, the trait focus at ICRISAT includes post rainy season adaptation encompassing terminal drought tolerance, genetic enhancement for high Fe and Zn contents in grain and sweet stalk traits for ethanol and animal feed production. Genetic and cytoplasmic diversification of hybrid parents for key traits is critical for sustaining the productivity across different production systems. The grain and stover quality need special attention in sorghum improvement research to enhance the market value of sorghum. A brief description is provided of the progress made at ICRISAT in partnership with national programs in recent years in these areas of sorghum genetic enhancement.